Concurrent severe fever with thrombocytopenia syndrome virus outbreaks on multiple fox farms, China, 2023 - Jian Sun; Lei Qian; Delong Li; Xiurong Wang; Hong Zhou; Cixiu Li; Edward C. Holmes; Jianke Wang; Juan Li; Weifeng Shi (Emerging Microbes and Infections)
The role of farmed animals in the viral spillover from wild animals to humans is of growing importance. Between July and September of 2023 infectious disease outbreaks were reported on six Arctic fox (Vulpes lagopus) farms in Shandong and Liaoning provinces, China, which lasted for 2–3 months and resulted in tens to hundreds of fatalities per farm. Severe Fever with Thrombocytopenia Syndrome Virus (SFTSV) was identified in tissue/organ and swab samples from all the 13 foxes collected from these farms. These animals exhibited loss of appetite and weight loss, finally resulting in death. In autopsy and histopathology, prominently enlarged spleens and extensive multi-organ hemorrhage were observed, respectively, indicating severe systemic effects. Viral loads were detected in various tissues/organs, including brains from 9 of the 10 foxes. SFTSV was also detected in serum, anal swabs, as well as in environmental samples, including residual food in troughs used by dying foxes in follow-up studies at two farms. The 13 newly sequenced SFTSV genomes shared >99.43% nucleotide identity with human strains from China. Phylogenetic analyses showed that the 13 sequences belonged to three genotypes, and that two sequences from Liaoning were genomic reassortants, indicative of multiple sources and introduction events. This study provides the first evidence of SFTSV infection, multi-tissue tropism, and pathogenicity in farmed foxes, representing an expanded virus host range. However, the widespread circulation of different genotypes of SFTSV in farmed animals from different provinces and the diverse transmission routes, highlight its increasing and noticeable public health risk in China.